Poet-Intellectual and Public Sociologist: An Interview with Zygmunt Bauman - Jacobsen, Michael Hviid; Tester, Keith (Academic Quarter | Akademisk kvarter, 2011)
Finally, this issue contains an interview, Poet-Intellectual and Public Sociologist, with Zygmunt Bauman by the Danish sociologist Michael Hviidand the British Keith Tester. Bauman has enriched our understanding of modernity, postmodernity and globalization. In this interview, asked about his audience, the Polish-born sociologist takes us through the different conceptions, especially those the Marxist tradition has developed about the place and role of intellectuals, their mission and importance to society. Bauman focuses specially on Adorno and uses him to emphasize that although we have definitely left behind the idea that intellectuals are historical agents of social transformation, we must not disregard the idea that intellectuals have something to say and that they can be important because we are confronted with suffering, threats and fear. The intellectual can have the privilege of being a detached observer.